2017
DOI: 10.1002/acr.23236
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in an Inception Cohort of Children With Juvenile Idiopathic Arthritis: A Longitudinal Analysis

Abstract: Objective. To describe changes in health-related quality of life (HRQoL) over time in children with juvenile idiopathic arthritis (JIA), relative to other outcomes, and to identify predictors of unfavorable HRQoL trajectories. Methods. Children with JIA in the Research in Arthritis in Canadian Children emphasizing Outcomes (ReACCh-Out) cohort were included. The Juvenile Arthritis Quality of Life Questionnaire (JAQQ, a standardized instrument), healthrelated Quality of My Life (HRQoML, an instrument based on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
4
40
0
2
Order By: Relevance
“…Pain as a predictor of unfavorable health‐related quality of life in children with JIA is widely studied . In a multinational quality‐of‐life study from the Pediatric Rheumatology International Trials Organization, pain was found to be a predictor of psychosocial well‐being .…”
Section: Discussionmentioning
confidence: 99%
“…Pain as a predictor of unfavorable health‐related quality of life in children with JIA is widely studied . In a multinational quality‐of‐life study from the Pediatric Rheumatology International Trials Organization, pain was found to be a predictor of psychosocial well‐being .…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 main approaches to identifying latent class trajectories within a heterogeneous population: group based trajectory model (GBTM) or growth mixture model (GMM) . These 2 approaches have been used to study juvenile arthritis, rheumatoid arthritis, and osteoarthritis . We chose GMM, as the concept of this model was consistent with our clinical observation that there is clustering of different disease courses.…”
Section: Methodsmentioning
confidence: 99%
“…In their explanation, the Task Force described shared decision making as follows: "the parents/patient must be informed about and agree with the selected target, the therapeutic options to reach the target and the reason for choosing the target, also in the light of the risks related to both the treatment and the disease". We strongly believe that nowadays, patients and parents could and should have a more active role in choosing targets and their personal treatment goals [24][25][26]. Ultimately, this will lead to better treatment adherence.…”
mentioning
confidence: 97%